Father's and mother's beliefs about children's anxiety - Beato, Ana (2022)
Previous research has focused on parenting styles and parental behaviors associated with children's anxiety. Parental beliefs about their child's anxiety have scarcely been studied, in spite of their probable influence in parents seeking help. The present study intended to fil that gap, by exploring what parents think about their children's anxiety and whether these cognitions are related or not to their use of professional help. Method: In‐depth semistructured interviews were conducted with 48 parents (50% fathers) of children (9–12 years old) with anxiety problems. Theoretical thematic analysis was performed on the transcripts. Results: Three dimensions were derived from the analysis, concerning (a) the causes of child's anxiety, (b) the impact of anxiety in the child's functioning, and (c) the evolution of anxiety. Most parents perceived the child's anxiety as a permanent condition, attributing it to external and parental factors and considering that the anxiety problems have a negative impact on the child's well‐being. Plus, parents who had previously sought professional help for the child's emotional problems tended to believe that anxiety could improve with child's or parents' efforts and with professional guid ance, contrarily to those who had not. Implications for research and clinical practice are discussed. Conclusion: The present study highlighted important parental beliefs about their children's anxiety that might influence their attitudes and decisions (e.g., seek for professional help). Other parental cognitions should be investigated in order to understand parenting in the context of childhood anxiety